Eastern perspectives on roles, responsibilities and filial piety: A case study. (May 2021) - Zhang, Liangwen; Han, Ying; Ma, Yonghui; Xu, Zhaoxu; Fang, Ya
Introduction: Broad issues relating to filial piety and ethical dilemmas of families and care practitioners in residential care were discussed as part of an international networking project. It is meaningful to explore the different roles and responsibilities of participants in residential care in the context of China's filial piety. Older residents and their children are part of this caring process, which might be significantly different from that in Western countries. However, only a little amount of research related to this topic has been conducted. Objective: This study aimed to identify and describe the roles and responsibilities of a nursing professional, manager, older person, and her children, as well as other mutual contacts in residential care, based on the context of Chinese filial piety culture. Methods: The study was conducted as a case study. The product of the analysis, themes, or categories that describe the phenomenon, content analysis method was applied. After a consultation with a group of experts on research on older adults, a specific nursing home was selected in Xiamen City, China. This case study emphasized the roles and responsibilities of a nursing professional, manager, the older resident, and her children as they related to the care of older adult. The data, which consisted of interviews with four participants, were collected using a semi-structured interview method. Inductive content analysis was applied to analyze data. Ethical considerations: Permission to conduct the interviews received ethical approval from the participating organization based on national standards. The elements of voluntary participation, anonymity, and confidentiality on the part of the respondent were explained. Findings: The analysis resulted in four participants, with some variation of roles and responsibilities, describing staffing level and competence and their behavior for reducing the accident of the older adult, and the children of older adult influencing the quality of taking care of the older adult, based on the filial piety. The nursing home residents were described as becoming increasingly complex with a subsequent demand for increased spiritual support. There was variation in roles and responsibilities among four participants, but their contributions adjusting was an overall focus. Manager plays a considerable role in the future development of the institution, as a resource allocator, and decision-maker. Nursing professional is the main personnel serving as a link among staffs. The older adult herself adjust mentally and actively with the aging process, and some of them can be able to burden in taking care of her grandchildren or can be rehired and still have a distinct role in society. Children are required to fulfill their obligations to their parents, which involves supports of care, spiritual and economy. Several factors such as managers and nursing professional competence and their cooperation, various aspects of supports from their children based on the filial piety, and adequate communication and self-adjusting of the older adult, were recognized as factors affecting the process of taking care of the older adult. Discussion: New information was produced to serve as theoretical guidelines in managing nursing homes, the training of nursing staff, preservation of the filial piety culture, and encouraging self-care among older people in the new era. Conclusion: A variety of roles and responsibilities for a nursing professional, manager, MrsWang and her children was identified in the older adult care process. Several factors to manager's and nursing professional's experience of the resource situation and competence level, and also adequate communication and self-adjusting of the older adult were suggested to affect the effect of taking care of the older adult. The older adults were perceived as more complex with more physical and mental problems but inadequate care from family members forcing the older adult from home care to a nursing home. A nursing home seems to have a higher nursing competence and be well-suited for the needs of the older adult, on the other hand, filial piety and self-care are also needed to play an important role in taking care of the older adult.